2001
DOI: 10.1002/lsm.1063
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of composite resins to enamel irradiated by the er:YAG laser: Application of the ultrasonic scaler on irradiated surface

Abstract: The tensile bond strength in the groups treated with the ultrasonic scaler exhibited approximately twice the strength observed in groups treated with laser irradiation alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 9 publications
0
39
0
2
Order By: Relevance
“…18,19,22,38 The potential role of subsurface damage and the limited hybridization in low tensile bone strength has been confirmed in laser-treated cavities; the superficial layer was removed by acid-etching or air abrasion. 21,24 Laser irradiation seems not to be able to create an inter-diffusion zone similar to that created by acid etching. 37,39,40 It is worth mentioning that verification, i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18,19,22,38 The potential role of subsurface damage and the limited hybridization in low tensile bone strength has been confirmed in laser-treated cavities; the superficial layer was removed by acid-etching or air abrasion. 21,24 Laser irradiation seems not to be able to create an inter-diffusion zone similar to that created by acid etching. 37,39,40 It is worth mentioning that verification, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…2,14,16,17 The recent literature has not precisely verified the superiority of laser irradiation to acid-etching for treating dentinal surfaces prior to bonding. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Previous reports have claimed that there are certain advantages in bonding to lased dentin because of an apparently enlarged surface area for adhesion based on the scaly and flaky surface appearance following Er:YAG irradiation. [33][34][35] In a study, the shear bond strength in deep lased dentin was better than in superficial lased dentin.…”
Section: Discussionmentioning
confidence: 99%
“…These superficial features are considered the main advantages attributed to use Er:YAG laser as an enamel conditioner, because it increases the retention between tooth surface and restorative material (Aoki et al, 1998;Dostalova et al, 1998;Visuri et al, 1996). Conversely, previous researches (De Munck et al, 2002;Eguro et al, 2001;Gonçalves et al, 2003;Martinez-Insua et al, 2000;Schein et al, 2003) have shown that the Er:YAG laser-irradiated layer can be disadvantageous for adhesion, mainly when it is applied in focused mode, since the excess of irregularities and fissures could influence on micromechanical retention of an adhesive system to substrate, reducing the tensile bond strength. Additionally, Er:YAG laser partially denatures the organic matrix and may block the diffusion pathway in enamel (Ying et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…Laser irradiation was performed in a noncontact mode for 20 s, 80 mJ of energy, 2 Hz of pulse repetition rate, as previously utilized in other studies (Eguro et al, 2001;Ying et al, 2004) to conditioning enamel surface. During the irradiation procedure, the air/ water spray was activated and the a 5 mL/min water flow (Delmé and De Moor, 2007) for cooling was adjusted by a control valve in the upper part of the laser handpiece (2,051), which is connected to the laser equipment by means of an optic fiber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation